A survey on the chronological evolution of timestamp schedulers in packet switching networks - Miaji, Yaser; Hassan, Suhaidi (2009)
The interest in solving the issue of congestion or flow control in network established from the first discovery and increase popularity of the Internet in 1967 or earlier. As the use of the network deployed and the popularity increase, the issue grows and the demand for an optimal or tentative solution becomes obvious. Since that time there has been an intensive effort from the scholars and researchers to solve the congestion control problem. The problem get worse by the engagement of novel traffic with different characteristics for application called realtime applications such as video and voice applications. Another cause of this demand is the user himself. The attempt in solving the congestion problem in network layer was popular in 90’s.This article will demonstrate chronologically how the attempts toward timestamp based scheduling in the packet-switch network have been evolved.Furthermore, the benefit and the drawbacks of using a mechanism will be presented. Also, a brief explanation of the mathematical, conceptual or implementation issue of a mechanism is given. The key success of the scheduler in the market will be highlighted. This paper will stimulate the research thinking to identify the importance and the ability of scheduling in routers to enhance quality of service (QoS) for real time application over other solution in several layers. In addition it will assist the researcher to distinguish the key failure of other proposed mechanisms which have not been implemented in real routers.